LIGHT Amplification by NF-κB Contributes to TLR3 Signaling Pathway-Induced Acute Hepatitis. (9th January 2023) - Lai, Dongming; Lv, Zejian; Lu, Xiaohua; Shang, Peng; Geng, Yunyun; Wang, Pu
Abstract : LIGHT is a member of the TNF superfamily and a proinflammatory cytokine involved in liver pathogenesis. Many liver diseases involve activation of Toll-like receptor 3 (TLR3), which is activated by double-stranded RNA (dsRNA). However, the involvement of LIGHT in TLR3 implicated liver diseases is not clear. In this study, we investigated the role of LIGHT in TLR3 involved liver pathogenesis by using a mouse model of TLR3 agonist poly(I:C)-induced hepatitis. We found LIGHT expression at both protein and mRNA level in liver tissues is dramatically increased during the course of poly(I:C)-induced liver injury. This induction depends on NF- κ B activation as pretreating the mice with a NF- κ B inhibitor abrogates LIGHT upregulation. Importantly, blockade of the LIGHT signaling pathway with the recombinant LIGHT receptor HVEM protein ameliorates liver injury in poly(I:C)-induced hepatitis. Conclusions . These results indicate that LIGHT amplification by NF- κ B plays a significant role in TLR3 involved hepatitis and points LIGHT to be a potential drug target for liver disease therapy.